Power conversion systems based on Brayton cycles for fusion reactors - Linares Hurtado, José Ignacio; Herranz Puebla, Luis Enrique; Moratilla Soria, Beatriz Yolanda; Serrano Remón, Ignacio Pablo (My University)
.

This paper investigates Brayton power cycles for fusion reactors. Two working fluids have been explored: helium in classical configurations and CO2 in recompression layouts (Feher cycle). Typical recuperator arrangements in both cycles have been strongly constrained by low temperature of some of the energy thermal sources from the reactor. This limitation has been overcome in two ways: with a combined architecture and with dual cycles. Combined architecture couples the Brayton cycle with a Rankine one capable of taking advantage of the thermal energy content of the working fluid after exiting the turbine stage (iso-butane and steam fitted best the conditions of the He and CO2 cycles, respectively). Dual cycles set a specific Rankine cycle to exploit the lowest quality thermal energy source, allowing usual recuperator arrangements in the Brayton cycle. The results of the analyses indicate that dual cycles could reach thermal efficiencies around 42.8% when using helium, whereas thermal performance might be even better (46.7%), if a combined CO2 H2O cycle was set.
Artículos en revistas